1999
DOI: 10.1002/(sici)1097-4636(19990915)46:4<465::aid-jbm4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of synthetic polymers on neutrophil migration in three-dimensional collagen gels

Abstract: In vitro studies of cell migration within three-dimensional polymeric materials are essential for understanding cell behavior and for developing new biomedical materials. Human neutrophil motility was examined in hydrated collagen gels containing various synthetic polymers. Physical mixtures of collagen and certain water-soluble polymers formed stable gels that were good substrates for cell migration. Addition of either polyethylene glycol (PEG) or the pluronictrade mark copolymer F68 did not change the morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
1
27
0
2
Order By: Relevance
“…Low doses may prime/activate PMNs, similar to any other foreign substance, while higher doses may prevent activation. P188 has been previously shown to attenuate neutrophil adhesion and transendothelial migration in vivo 14, 16, 17 , prompting the hypothesis that P188 may interact with the cell membrane or adhesion molecule, acting as a competitive inhibitor of adhesion molecule interactions. The poloxamer may be acting in a similar fashion at very high doses in our study, preventing some level of NADPH independent activation by PMA and preventing interaction between the adhesion molecule and the antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low doses may prime/activate PMNs, similar to any other foreign substance, while higher doses may prevent activation. P188 has been previously shown to attenuate neutrophil adhesion and transendothelial migration in vivo 14, 16, 17 , prompting the hypothesis that P188 may interact with the cell membrane or adhesion molecule, acting as a competitive inhibitor of adhesion molecule interactions. The poloxamer may be acting in a similar fashion at very high doses in our study, preventing some level of NADPH independent activation by PMA and preventing interaction between the adhesion molecule and the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…15 Tan and coworkers subsequently showed that neutrophil migration was inhibited by synthetic polymers in an in vitro , three-dimensional collagen gel. 14 Lane and colleagues followed their original work by assessing PMN migration in vivo after P188 treatment in a rodent model of bacterial sepsis. 16 They found a significantly increased mortality among rodents treated with P188 and attributed this to impaired neutrophil delivery to the inflammatory locus and a subsequent increased rate of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan and Saltzman 43 reported that P-188 decreased neutrophil migration on a collagen matrix, as well as random cellular motion. The poloxamer, however, did not inhibit neutrophil migration in the absence of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…22 Poloxamers have also been reported to have antiinflammatory effects in certain model systems. 30,43 Their antiinflammatory effect can derive from modulation of any of the following stages in the inflammatory process: 1) interference with intercellular adhesion molecule-mediated leukocyte margination; 2) modulation of the cytokine response; 3) modulation of chemotaxis; 4) blocking of opsonization; and 5) modulation of phagocytosis. The majority of studies involving the immunological effects of poloxamers have been focused on their effects on cell migration and phagocytosis.…”
Section: Discussionmentioning
confidence: 99%